Environmental Geochemistry of the Surface Sediments of Sabkhat Daryana, NE Libya - Shaltmi, Osama; Errishi, Hwedi; Fares, Fares (Libyan Journal of Science &Technology, 2022)
The present paper discriminates between nearshore and farshore sabkha sediments at Daryana Coast, NE Libya, using geochemical viewpoints. The nearshore sediments are mostly sand with low amounts of mud (Al). High contents of heavy metals found in these sediments can be due to their incorporation in carbonate phases. The farshore sediments are mostly sandy mud with higher contents of Al and lower contents of heavy metals, except higher contents of Pb. The heavy metals are mainly of anthropogenic origin (EF > 1.5). Generally, Igeo values indicate that the study area is unpolluted with most heavy metals (except with As and Hg).